FAKTOR-FAKTOR YANG MEMENGARUHI PEMANFAATAN LAYANAN KESEHATAN PADA PASIEN HIPERTENSI DI PUSKESMAS KECAMATAN MAMPANG PRAPATAN SAAT PANDEMI COVID-19 - Rachma Hermawan (2022)
After almost two years have passed, the Covid-19 pandemic has had such a farreaching impact, one of which is a decrease in patient visits to various health care facilities which has led to an increase in the burden of the disease. The trend of visiting hypertensive patients at the the Puskesmas Kecamatan Mampang Prapatan in 2019-2021 tends to decrease. Hypertension is also the single major contributor to diseases with the largest burden of disease from death and disability in the world. This study aims to determine the facto-factors that affect the use of health services in hypertensive patients at the the Puskesmas Kecamatan Mampang Prapatan during the Covid-19 pandemic. This type of research uses observational analytical studies with a cross-sectional design. The total sample of 53 respondents was taken using the consecutive sampling technique. Based on the chi-square test analysis, it was obtained that there was no relationship between hypertension knowledge (p=0.284), mileage (p=0.963), and healthy and sick perceptions (p=1.00) with the utilization of health services. There is a relationship between comorbid diseases (p=0.001) and the utilization of health services which may be caused by the increasing need due to the decreased quality of life of patients due to comorbidities. The group of respondents who did not have comorbid diseases were at risk of irregularity in the utilization of health services 7.92 times greater than respondents who had comorbid diseases. This finding may be due to comorbidities that can significantly reduce the patient's quality of life thereby increasing the need of utilize health services.